The Role of Bhabinkamtibmas in Preventing the Crime of Theft with Weights in the Jurisdiction of the Tulungagung Police (Indonesian Journal of Police Studies, 2024)
Indonesia is a fairly large country and has a rich cultural diversity and traditions. One of the striking aspects is the high level of welfare that is taking place in society, especially the economic disparity. Tulungagung district is a district frequently visited by foreigners with a high level of theft crime with high reporting. It shows that people are still less aware of their own vehicles. The formula problem in this final task is how the efforts of Bhabinkamtibmas members through the approval with the purpose of research to be able to describe the implementation of the activities of the Bhabinkaamtibamas through approval in raising public awareness to prevent the occurrence of theft cases with the location of research in the legal territory of Polres Tulungagung. This research uses qualitative methods, as the theory and the concepts used to analyze these problems are role theory, management theories, theory of routine activity, the concept of theft, and the Bhabinkamtibmas concept. Data collection techniques that can be used are interviews, and document study. The result was found that the cause of the rise in the number of theft with warnings is the lack of awareness of the public in creating a safe situation in its territory and lack of competence of Bhabinkamtibmas members in carrying out service to the public. This can be seen from the 257 members of only 8 members who have already followed Binmas Education. Advice to Polres Tulungagung to implement the system of Reward and Punishment, provide vocational education training to members of Bhabinkamtibmas, and increase the number of visits and the quality of material given to the community.
Keywords: Kata Kunci : Peran, Bhabinkamtibmas, Penyuluhan, Pencegahan